2018
DOI: 10.1183/13993003.01592-2017
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette vapour enhances pneumococcal adherence to airway epithelial cells

Abstract: E-cigarette vapour contains free radicals with the potential to induce oxidative stress. Since oxidative stress in airway cells increases platelet-activating factor receptor (PAFR) expression, and PAFR is co-opted by pneumococci to adhere to host cells, we hypothesised that E-cigarette vapour increases pneumococcal adhesion to airway cells.Nasal epithelial PAFR was assessed in non-vaping controls, and in adults before and after 5 min of vaping. We determined the effect of vapour on oxidative stress-induced, PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(110 citation statements)
references
References 29 publications
2
103
0
3
Order By: Relevance
“…82 The increased levels of nasal PAFR were seen in adults inhaling E-cigarette vapour for 5 minutes. 83 ECVE (with or without nicotine) also increase pneumococcal adhesion to a human epithelial cell line, and this was related to ROS production. Since pneumococcal infection is the commonest cause of bacterial pneumonia, E-cigarette use has the potential to facilitate pneumococcal diseases.…”
Section: Effects Of E-cigarettes On Resistance To Infectionmentioning
confidence: 91%
See 1 more Smart Citation
“…82 The increased levels of nasal PAFR were seen in adults inhaling E-cigarette vapour for 5 minutes. 83 ECVE (with or without nicotine) also increase pneumococcal adhesion to a human epithelial cell line, and this was related to ROS production. Since pneumococcal infection is the commonest cause of bacterial pneumonia, E-cigarette use has the potential to facilitate pneumococcal diseases.…”
Section: Effects Of E-cigarettes On Resistance To Infectionmentioning
confidence: 91%
“…Platelet‐activating factor receptor (PAFR) is used by pneumococci to adhere to host cells, and CS increases pneumococcal adhesion by up‐regulating PAFR expression in human lower epithelial cells (Table ) . The increased levels of nasal PAFR were seen in adults inhaling E‐cigarette vapour for 5 minutes . ECVE (with or without nicotine) also increase pneumococcal adhesion to a human epithelial cell line, and this was related to ROS production.…”
Section: Effects Of E‐cigarettes In Humansmentioning
confidence: 99%
“…62 Notably, PAFR expression is increased in response to environmental exposures, in particular CS, air pollution, acids, viral infections, 60,63 welding fumes 64 and e-cigarette vapour. 65 Crucially, PAFR protein is increased in the large and small airways of COPD patients and correlates with current and previous smoking history. 51,66 The bacterial adhesion enabled by the PAFR is directly linked to increased susceptibility to infection by both Gram-positive and Gram-negative bacteria.…”
Section: Role Of Pafr In Bacterial Persistencementioning
confidence: 99%
“…Although little is known of the effects of PAF itself in the airways, the PAFR plays crucial roles in biological processes, including vasodilation, cell proliferation and angiogenesis, and in regulating inflammatory responses . Notably, PAFR expression is increased in response to environmental exposures, in particular CS, air pollution, acids, viral infections, welding fumes and e‐cigarette vapour . Crucially, PAFR protein is increased in the large and small airways of COPD patients and correlates with current and previous smoking history .…”
Section: Bacterial Colonization and Infection In Copdmentioning
confidence: 99%
“…The exposure to EV was shown to induce biofilm formation, hydrophobicity, and adherence to epithelial cells by S. aureus [20]. In another study, EV exposure was shown to facilitate pneumococcal host epithelial adherence via significant upregulation of platelet activating factor receptor (PAFR) in nasal epithelial cells from vapers, as well as in EV-exposed A549 lung carcinoma cell line [21]. Notably, the effects of EV exposure on the transcriptome and the pathogenesis of S. pneumoniae are largely undefined.…”
Section: Introductionmentioning
confidence: 99%